Analisis Faktor yang Berhubungan dengan Kelelahan Kerja Subjektif Pada Pekerja di PT. X - Cahyani, Cherry Indira; Sahri, Moch (Poltekkes Kemenkes Jambi, 2024)
Background: Work fatigue is a condition that is different for each individual, but all of these individuals experience loss of efficiency, decreased work capacity, and endurance. The purpose of this study was to analyze factors related to work fatigue in production workers at PT. X. Methods: This research is a quantitative study with a cross-sectional approach with a total sampling technique for production workers at PT. X totaled 40 respondents. Data collection was obtained from primary data in the form of an IFRC Result: The results of statistical tests using Spearman's rank show that the factors of age, length of work, and workload have a relationship with work fatigue, while there is no relationship with work fatigue on length of service. At the level of work fatigue, the majority of workers experience moderate work fatigue. Conclusion: So it is advisable for companies to provide work according to individual capacity based on the age of the worker, overtime hours do not exceed the specified regulations, then provide a workload that is in accordance with the capacity of the worker by not giving multiple jobs.